Family listening/circle program: The experience of community action projects to promote family and community wellness in three tribal communities in New Mexico - Rebecca Rae; Lorenda Belone; Eleanor Tafoya; Melissa Yepa; Benalda Cohoe-Belone; Ira Burbank; Ardena Orosco; Pius Lacroix-Garcia; Mingma Sherpa; Nina Wallerstein (Frontiers Media S.A., 2023)
IntroductionThe Family Listening/Circle Program (FLCP) is a community-based participatory research (CBPR), culture-centered, intergenerational family strengthening program that was co-developed in partnership with the University of New Mexico's Center for Participatory Research (UNM-CPR) and three tribal communities (Pueblo of Jemez, Ramah Navajo, and Mescalero Apache) in New Mexico. The Family Listening/Circle Program brings together fourth and fifth graders, their parents, caregivers, and elders to reduce risky behaviors associated with the initiation of substance use among the youth, and to strengthen family communication and connectedness to culture and language as protective factors.MethodsThe tribal research teams (TRTs) from each community worked with UNM-CPR to co-create, pilot, implement, and evaluate the tribally-specific FL/CP curricula centered in their own tribal histories, language, knowledge, visions, and actions for the future. A key component of the FL/CP involved the planning and completion of community action projects (CAPs) by participating families. During the final session of the program, the families present their community action projects on poster boards, with children leading the presentations. The TRTs and UNM team document narratives of what was shared and learned by the families.ResultsThe CAPs provide an empowerment and community benefit focus based on Paulo Freire's philosophy that people can become agents of change if they identify and work on issues that are important to them. The community action projects are also centered in Indigenous values and practices of reciprocity, responsibility, and being active members of the community.DiscussionThe CAPs added unique contributions to the Family Listening/Circle Program as the participants' learnings were strengthened when they had the opportunity to give back to their communities. The CAPs were important to document as they illustrated the potential range of effectiveness with their capacity to empower participants to address challenges within their communities, strengthen cultural norms and values, and improve the wellbeing of community members.